The complete plastid genomes of two Fabaceae orphan crops from Africa - Xuezhu Liao; Yang Liu; Huan Liu (Mitochondrial DNA. Part B. Resources, 2019)
Dolichos bean (Lablab purpureus) and Bambara groundnut (Vigna subterranea) are two traditional crops from Africa with important economic values. The study of such neglected or underused crops (orphan crops) should contribute to the resolution of food shortage in Africa. Here we assembled and described the complete plastid genome of the two Fabaceae orphan crop species. The length of the complete plastomes of L. purpureus and V. subterranea is 151,753 bp and 152,015 bp, respectively. Maximum-likelihood (ML) phylogenetic analyses indicated that L. purpureus and Phaseolus vulgaris are closely related, and V. subterranea and other Vigna species are clustered in one clade, which is congruent with former studies.